The strengths and weaknesses of simplicity - Kim Ebensgaard Jensen (Globe, 2019)
Review of Birger Andersen, Basic English Grammar, 3rd ed. Frederiksberg: Samfundslitteratur, 2018, 228 pp., ISBN: 978-87-593-3204-7